Transformation of the European migration policy in terms of global and regional challenges - Adamyk, Viktoriia; Stakhova, Nataliia (Herald of Economics, 2022)
Introduction. The migration crisis in Europe, which began a few years ago as a result of a massive influx of refugees from Syria and other countries of the Middle East and Africa, showed an escalation in 2022 in connection with the unprovoked Russian-Ukrainian war. Migration policy, which has evolved over decades under the influence of internal and global challenges, needs to be reformed in order to adapt to new realities.The purpose of the article is to study the evolution of European migration policy and the prospects for its reform in the context of the Russian-Ukrainian war.Research methods. To achieve the goal set in the article, general scientific and special methods were used, namely: analysis and synthesis, induction and deduction, abstraction and concretization, systematization, as well as elements of comparative analysis. The methodological basis for the research is the national legal acts of the EU countries and joint documents regulating the processes of migration and integration of immigrants into European society, scientific works of domestic and foreign researchers, statistical reports, etc.Results. The trends of international migration considered in the article are characterized by a rapid increase in its volume and a change in form from mainly labor migration to an influx of refugees and people seeking refuge due to political, mostly military conflicts in the regions of origin. Not only the working-age population is displaced, but also children and elderly people who need social support but do not apply for places on the labor market. Cities, mainly large agglomerations, remain the main destinations. The burden on the state and local budgets of the recipient countries, social, transport and household infrastructure increases every year, and the levers of the European migration policy show insufficient effectiveness. The transformation of the migration policy in the EU is taking place in the direction of partial harmonization and consolidation of efforts to prevent the negative consequences of the mass influx of refugees, as well as their gradual integration into European society. The article examines the peculiarities of the national immigration policy in individual EU countries and the difficulties of its implementation in modern conditions; the need to use an inclusive approach to migrants from Ukraine is indicated.Discussion. It is important to focus future research on studying the experience of countries that are the main destinations for migrants from Ukraine, in order to level the negative consequences of their influx and improve the system of levers for the integration of refugees into the national and common European economic systems.